EFEKTIVITAS PEMBELAJARAN INQUIRY TERHADAP HASIL DAN AKTIVITAS BELAJAR SISWA MTsN SAKTI KOTA BAKTI KABUPATEN PIDIE - Samsul Kamal; Jailani Jailani; Rahmi Rahmi (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2012)
Paradigm of education requires a better change in students’ behavior. To challenge these problems, the improvement way of learning is needed. Inquiry method is associated to improve student learning outcomes and activities. The purpose of this study was to determine the differences of student learning outcomes and activities that is learned between the inquiry method and conventional learning. The population of this study was all students from five classes in grade VII MTsN Bakti Pidie City academic year of 2010/2011. The samples were randomly selected (random sampling) with VII2 grade students as the experimental group and VII4 grade students as a control group. The data was collected through paper and pencil test: pretest and posttest and non-test through observation sheet. The data is analyzed using t-test, moreover student activities were analyzed by percentage formula. The analysis of data shows t count= 3.80 and ttable = 2.64, it is indicated that the student learning outcomes by methods of inquiry is significantly different from student learning outcomes with conventional methods. Students teaching by Inquiry learning are more active than students teaching by conventional learning.